Effect of 10% sodium bicarbonate on bond strength of enamel and dentin after bleaching with 38% hydrogen peroxide - Fernanda Medeiros Darzé; Flávia Lucisano Botelho do Amaral; Fabiana Mantovani Gomes França; Cecília Pedroso Turssi; Roberta Tarkany Basting
AbstractIntroductionBy-products of hydrogen peroxide degradation released during dental bleaching influence the polymerization of adhesive systems and composite resins, causing a reduction in shear bond strength to the tooth.Objectivethe aim of this article was to evaluate the effect of 10% sodium bicarbonate (SB), applied for different lengths of time, on the shear bond strength to enamel and dentin after bleaching.Material and methodEnamel and dentin blocks were divided into groups (n=10): (1) control: no bleaching; (2) immediate: bleaching immediately followed by restoration; (3) 14-day: bleaching, restoration 14 days later; (4) SB for 10 minutes: bleaching, SB gel for 10 minutes, immediately followed by restoration; (5) SB for 20 minutes: bleaching, SB gel for 20 minutes, immediately followed by restoration. A 38% hydrogen peroxide gel (Opalescence Boost/Ultradent) was used. After application of the adhesive system, composite resin cylinders were mounted on the surface of the substrates in order to test shear bond strength. Result: ANOVA and Tukey tests showed significantly higher mean enamel bond strength values for the 14-day follow-up group and without significant differences for control group. Mean bond strength values obtained for the other groups were intermediate. When testing dentin, the Tukey test revealed a significantly higher mean bond strength value for the 14-day follow-up group when compared with application of SB for 20 minutes.ConclusionSB gel applied was unable to reverse the low bond strength to enamel and dentin after bleaching treatment.